2022
DOI: 10.1186/s12909-021-03082-z
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of interprofessional identity formation in dental hygienists: an exploratory case study

Abstract: Background In a super-aging society, medical-dental collaboration is increasingly vital for comprehensive patient care. Particularly in dysphagia rehabilitation and perioperative oral functional management, dental hygienists’ active involvement is pivotal to interprofessional collaborative practice. Despite this societal expectation, dental hygienists’ experiences and perceptions of interprofessional collaboration have not been explored. This study aims to investigate dental hygienists’ interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Their text data included "improving and maintaining oral health that is closely related to everyday life, such as eating, speaking and laughing", and the "improvement of the overall health and quality of life through oral health". This result is consistent with that of the study by Imafuku et al, that explored the identity formation processes of dental hygienists in the field as interprofessional collaborators [19]; however, the significance of this research is that it showed that such a change in perception might be occurring among the undergraduate students.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Their text data included "improving and maintaining oral health that is closely related to everyday life, such as eating, speaking and laughing", and the "improvement of the overall health and quality of life through oral health". This result is consistent with that of the study by Imafuku et al, that explored the identity formation processes of dental hygienists in the field as interprofessional collaborators [19]; however, the significance of this research is that it showed that such a change in perception might be occurring among the undergraduate students.…”
Section: Discussionsupporting
confidence: 92%
“…This study was approved by the University of Shizuoka Research Ethics Committee [approval number [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Furthermore, informed consent was provided by all the study participants.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Here is a critical analysis of this topic: 1) Self-Reflection, social media platforms allow individuals to share personal thoughts, experiences, and opinions. 27 A critical analysis would explore the extent to which individuals engage in self-reflection while using social media and examine the factors that may hinder or facilitate this process. 28 2) Metacognitive Awareness refers to individuals' understanding and awareness of their own thinking processes.…”
Section: Schoolsmentioning
confidence: 99%